Mathnāwi-yi Shīrīn u Farhād - Jarūnī, Salīmī, (Miras Maktoob, ISBN: 9789004365452., 2019)
In the history of Persian literature, one finds quite a number of works by famous authors which later served as a model for similar works by other writers. By way of example one could mention Firdawsī's (d. 411/1020) Shāh-nāma and Niẓāmī's (d. 608/1209) Iskandar-nāma , Saʿdī's (d. 691/1291-92) Gulistān and Jāmī's (d. 898/1492) Bahāristān , or Farīd al-Dīn ʿAṭṭār's (d. 618/1221) Manṭiq al-ṭayr and Mīr ʿAlī Shīr Navāʾī's (d. 906/1501) Lisān al-ṭayr . In the case of the mathnawī contained in the present volume, it was Niẓāmī's Khusraw u Shīrīn which served as the model for Shīrīn u Farhād , a romantic epos by the otherwise unknown 9th/15th-century poet Salīmī Jarūnī. A native of Hormuz (formerly Jarūn), he dedicated his poem in 880/1475 to the local sultan of his days, Salgharshāh. Its language is unpretentious and the native ambiance is sometimes palpable. Its heros are pure of heart, and a mystical thread runs throughout the poem.